Survival as a clinical outcome and its spiritual significance in a cohort of patients with advanced central pelvic neoplastic disease undergoing total pelvic evisceration: a poorly debated issue - Macciò, Antonio; Sanna, Elisabetta; Piras, Roberta; Lavra, Fabrizio; Vallerino, Valerio; Maricosu, Giovanni; Giglio, Emanuela; Mura, Antonio; Tidore, Marcello; Madeddu, Clelia (Frontiers in Medicine, 2023)
Background Patients with either treatment-resistant or relapsing advanced central pelvic neoplastic disease present with a condition responsible for debilitating symptoms and consequently poor quality of life (QoL). For these patients, therapeutic strategies are very limited and total pelvic evisceration is the only option for relieving the symptoms and increasing survival. Of note, taking charge of these patients cannot be limited to increasing their lifespan but must also be aimed at improving the clinical, psychological, and spiritual conditions. This study aimed to prospectively evaluate the improvement in survival and QoL, focusing on spiritual wellbeing (SWB), in patients with poor life expectancy who underwent total pelvic evisceration for advanced gynecological cancers at our center. Patients and methods The QoL and SWB were assessed using the European Organisation for Research and Treatment of Cancer QoL questionnaire (EORTC QLQ-C30), EORTC QLQ-SWB32, and SWB scale, which were repeatedly administered: 30 days before surgery, 7 days after the procedure, 1 and 3 months after surgery, and then every 3 months until death or the last follow-up assessment. Operative outcomes (blood loss, operative time, hospitalization, and incidence of complications) were evaluated as secondary endpoints. The patients and their families were included in a dedicated psycho-oncological and spiritual support protocol, which was managed by specifically trained and specialized personnel who accompanied them during all phases of the study. Results A total of 20 consecutive patients from 2017 to 2022 were included in this study. Of these patients, 7 underwent total pelvic evisceration by laparotomy and 13 underwent laparoscopy. The median survival was 24 months (range: 1–61 months). After a median follow-up of 24 months, 16 (80%) and 10 patients (50%) were alive at 1 year and 2 years after surgery, respectively. The EORTC-QLQ-C30 scores significantly improved yet at 7 days and at 1, 3, 6, and 12 months, as compared with the preoperative values. In particular, an early improvement in pain, overall QoL, and physical and emotional functions was observed. With respect to the SWB, the global SWB item score of the EORTC QLQ-SWB32 questionnaire significantly increased after 1 month and 3 months, as compared with preoperative values (p = 0.0153 and p = 0.0018, respectively), and remained stable thereafter. The mean SWB scale score was 53.3, with a sense of low overall SWB in 10 patients, a sense of moderate SWB in eight patients, and a sense of high SWB in two patients. The SWB scale score significantly increased after 7 days, 1 month, and 3 months, as compared with the preoperative value (p = 0202, p = 0.0171, and p = 0.0255, respectively), and remained stable thereafter. Conclusion Total pelvic evisceration is a valid approach for improving both survival and QoL in selected patients with advanced pelvic neoplasms and poor life expectancy. Our results particularly underline the importance of accompanying the patients and their families during the journey with dedicated psychological and spiritual support protocols.